Impact of international financial liberalisation on economic growth : the case of CARICOM - Greenidge, Kevin ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2001)
Demonstrates the significance of international financial liberalisation on economic growth in the Caribbean over the period 1979-1999.